2015
DOI: 10.1104/pp.15.01214
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis Chloroplast stromal N-terminome; complexities of N-terminal protein maturation and stability

Abstract: ORCID IDs: 0000-0003-4756-9125 (E.R.); 0000-0001-5402-7725 (J.K.); 0000-0002-6395-2610 (N.H.B.); 0000-0001-9536-0487 (K.J.v.W.).Protein amino (N) termini are prone to modifications and are major determinants of protein stability in bacteria, eukaryotes, and perhaps also in chloroplasts. Most chloroplast proteins undergo N-terminal maturation, but this is poorly understood due to insufficient experimental information. Consequently, N termini of mature chloroplast proteins cannot be accurately predicted. This mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
107
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(124 citation statements)
references
References 83 publications
(137 reference statements)
17
107
0
Order By: Relevance
“…The FtsH protein set highlighted in Figure 6 are the same proteins that are highlighted in the protein domain set FtsH (IPR016135), which was one of the fastest degrading domain groups in our analysis (Table 2). These proteases have direct roles in the turnover of the photosynthetic apparatus and in plastid thylakoid formation (Zaltsman et al, 2005;Kato et al, 2012;Rowland et al, 2015). It has been reported that mRNA for FtsH1, FtsH2, FtsH5, and FtsH8 generally increases in young developing leaves (Zaltsman et al, 2005).…”
Section: Protein Abundance and Turnover Changes In Young Leaves Withmentioning
confidence: 99%
“…The FtsH protein set highlighted in Figure 6 are the same proteins that are highlighted in the protein domain set FtsH (IPR016135), which was one of the fastest degrading domain groups in our analysis (Table 2). These proteases have direct roles in the turnover of the photosynthetic apparatus and in plastid thylakoid formation (Zaltsman et al, 2005;Kato et al, 2012;Rowland et al, 2015). It has been reported that mRNA for FtsH1, FtsH2, FtsH5, and FtsH8 generally increases in young developing leaves (Zaltsman et al, 2005).…”
Section: Protein Abundance and Turnover Changes In Young Leaves Withmentioning
confidence: 99%
“…Upon arrival in the stroma, SPP binds with a broad spectrum of specificity to the transit peptides and removes them by a single endoproteolytic reaction, with subsequent release of the mature proteins but not the transit peptides Lamppa, 1999, 2002). Recent proteome analysis showed that a substantial number of stromal proteins have multiple distinct N termini, implying the presence of multistep N-terminal processing mechanisms or simply reflecting SPP's imprecise site specificities (Rowland et al, 2015). The cleaved transit peptides are subjected to additional trimming into smaller fragments by SPP and are degraded further by PrePs and OOPs in the stroma (Teixeira and Glaser, 2013; Fig.…”
Section: Sequential Proteolytic Events For Preprotein Processing Andmentioning
confidence: 99%
“…Early observations in yeast led to the formulation of the N-end rule, which states that certain amino acids, when exposed at the N terminus of a protein, act as triggers for degradation (Bachmair et al, 1986). An N-end rule for chloroplasts/plastids in plants is not known but certainly is a possibility (Apel et al, 2010;Rowland et al, 2015).…”
mentioning
confidence: 99%